Seasonal dynamics in the diet of pelagic fish species in the southwest Baltic Proper. (24th December 2016) - Jakubavičiūtė, Eglė; Casini, Michele; Ložys, Linas; Olsson, Jens
Abstract : There is accumulating evidence of the significant role of three-spined sticklebacks ( Gasterosteus aculeatus ) for ecosystem structure and functioning in coastal areas of the Baltic Sea, but little is known about the role of the species in the pelagic foodwebs of the Baltic and its interaction with other planktivorous fish species. In this study, we assess the feeding niche, diet overlap, and prey selectivity of sticklebacks, herring ( Clupea harengus ), and sprat ( Sprattus sprattus ) in an area of the southwest Baltic Sea (Kalmar Sound) in relation to the seasonal abundance of zooplanktonic prey during 2009–2011. The main prey items for all fish species studied were the calanoid copepods Eurytemora affinis, Temora longicornis, and Acartia spp. during spring and summer, and the cladoceran Bosmina spp in autumn. The diet of all the three fish species overlapped considerably, especially during summer and autumn. A substantial diet overlap was even present between sticklebacks and larger (>10 cm) herring and sprat. We also found evidence for an overlap in feeding preferences, i.e. certain zooplankton species were selected by all the three fish species in each given season. Overall, these results indicate potential resource competition between sticklebacks and clupeids. With an increasing abundance of sticklebacks in the Baltic Sea, their role should not be neglected when investigating pelagic foodweb dynamics, and management of herring and sprat may have to account for sticklebacks by considering that sticklebacks, via food competition, might affect clupeid stocks.